Bureaucratic Reform and Dynamic Goernance for Combating Corruption: The Challenge for Indonesia - Kasim, Azhar (UI Scholars Hub, 2013)
This paper discusses the current government bureaucratic problems in Indonesia that are multi-dimensional and protracted as a vicious circle. Government bureaucracy reform efforts in Indonesia will not be successful if they are still carried out in linear mindset that does not address the root of the problem. This paper also discusses how systemic and dynamic approaches to good governance can create the leverage to get rid of vicious circle in innovative ways. The result is in order to solve this complex and dynamic problem we need more comprehensive strategies which include four major areas, that is, political leadership, public policy harmonization (including rules and regulations), the application of merit system in all government agencies, and anti corruption movement.